Collagenase injection into the suprachoroidal space of the eye to expand drug delivery coverage and increase posterior drug targeting. (December 2019) - Jung, Jae Hwan; Park, Sanghyun; Chae, J. Jeremy; Prausnitz, Mark R.
Abstract: Injection into the suprachoroidal space (SCS) allows drug delivery targeted to sclera, choroid, and retina. Here, we studied SCS injection formulated with collagenase to expand drug delivery coverage and increase posterior drug targeting within SCS by breaking down collagen fibrils that link sclera and choroid in the SCS. When 1 μm latex microparticles were injected with a collagenase formulation using microneedles into the SCS of rabbit eyes ex vivo and incubated at 37 °C for 4 h, microparticle delivery coverage increased from 20% to 45% and enhanced posterior drug targeting. Collagenase concentration was optimized to 0.5 mg/mL to maximize expanded posterior delivery and minimize tissue damage. Effects of collagenase injection within SCS increased and then plateaued 4 h after injection. Simultaneous injection of collagenase and microparticles had a greater effect on expanded delivery in the SCS compared to sequential injection. Collagenase injection into the SCS of rabbit eyes in vivo was also effective to expand delivery and was generally well-tolerated, showing transiently lowered IOP, but no apparent lasting adverse effects on ocular tissues such as sclera, choroid, and retina, as determined by analyzing histology, sclera tensile strength, and fundus imaging. We conclude that addition of collagenase during SCS injection can expand drug delivery coverage and increase posterior drug targeting. Graphical abstract: Image 1 Highlights: Drug delivery in the suprachoroidal space (SCS) can target chorioretinal tissue. The sclera and choroid, which bound SCS, are connected by loose collagen fibrils. Collagenase delivery to SCS expanded drug delivery coverage by digesting collagen. Collagenase delivery to SCS increased drug targeting to the posterior SCS. Collagenase formulation was well tolerated by the rabbit eye in vivo.